Compact polyelectrolyte hydrogels of gelatin and chondroitin sulfate as ion's mobile media in sustainable all-solid state electrochemical devices. Issue 7 (7th October 2020) - González, Jimena S.; Burlaka, Arsen; Paz, José; Salavagione, Horacio J.; Carretero-González, Javier; Hernández, Rebeca
Abstract : Design of an electrochemical cell based on a sustainable biopolymer hydrogel and graphene electrodes for potential applications in bioelectronics. Abstract : The creation of flexible and high strength hydrogel materials from natural polymers as low cost and safe solid electrolytes is an area of intense research nowadays. We present a novel approach for the preparation of gelatin and chondroitin sulfate hydrogel complexes by using a simple centrifugation process. The innovative dual-bio-gel-network is able to swell and shrink upon changes on the pH and NaCl concentration. The solid bio-gels sandwiched between two macroporous carbon electrode materials are assembled in symmetric cells and their electrochemical properties are evaluated by cyclic voltammetry, galvanostatic, and impedance spectroscopy measurements. The cells exhibit areal capacitance values up to 2.74 mF cm −2 (3.1 F g −1 ) and a low resistance value of 12 Ohm cm 2 for graphene electrode materials. These properties are the consequence of the successful infiltration of the solid gel inside the porous structure of the carbon electrode that boosts the charge transfer at the biopolymer/carbon electrode interphase. The results obtained may provide additional inspiration in the emerging field of bioelectronics, where biocompatible and powered systems are of the utmost importance.